Assessing the impact of binaural and non-binaural auditory beat intervention to pain and compression in mammography. Issue 1 (January 2023) - Nelson, D.; Berry, R.; Szczepura, K.; Mercer, C.E.
Abstract: Introduction: Pain and discomfort has a negative impact on a patient's overall experience and may impact on subsequent re-attendance to mammography. Pain during mammography remains a significant issue. Assessment of interventions to reduce levels of pain associated with mammography are essential to increase attendance to breast services and improve user experience. Methods: Participants (n = 60) were invited to take part in the study at one hospital Trust within the UK. Postal invitations were sent 2 weeks prior to appointment to patients older than 40 years with previous mammography attendance at the same Trust to allow for comparison of previous and current pain scores/compression values. Patients were randomised into 3 groups: Binaural music (BM), non-binaural music (NBM) and standard care (C). A numerical rating scale (NRS) was used to rate pain. Results: Patient tolerance is increased by the application of both the non-binaural and binaural music. Binaural music was most effective in improving patient tolerance (p = 0.02). When applied compression increased some patients recorded less pain, which may have implications to image quality and radiation dose for patients. Binaural music reduces the perception of mammographic pain within this data set. Conclusion: 5 min exposure to binaural music improves patient experience and tolerance for mammography which could be utilised to improve attendance rates in screening and symptomatic services. Implications for practice: There is an indication for further research looking at application prior and during interventional biopsies. Music intervention can be offered to patients in the severe pain category who refuse mammography. It is acknowledged from these findings that the introduction of BM and NBM prior to mammography would be a low risk, cost effective intervention within the hospital setting.